Method for recovering composition of molten salt composition and method for producing chemically strengthened glass

By vibrating the addition of the container-filled sodium metal ion adsorbent in the molden salt bath, the problem of low recovery efficiency of the molden salt bath composition is solved, extending the service life of the molden salt bath and improving the chemical strengthening effect.

JP7663017B2Active Publication Date: 2025-04-16AGC INC
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2021078096
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-04-30
Publication Date
2025-04-16
Estimated Expiration
2041-04-30

AI Technical Summary

Technical Problem

The prior art is difficult to efficiently restore the composition of the molten salt bath, resulting in a decrease in the chemical strengthening effect of chemically strengthened glass, and the service life of the molten salt bath is relatively short.

Method used

By filling the sodium metal ion adsorbent in the addition container and vibrating the addition container in the molten salt bath, the vibration width, speed and time are controlled to improve the contact efficiency of the adsorbent with the molten salt bath, reduce the concentration of small sodium metal ions, and increase the concentration of large sodium metal ions.

Benefits of technology

It effectively extends the service life of molten salt bath, improves the chemical strengthening effect of chemically strengthened glass, and increases the number of chemical strengthening times.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007663017000004
    Figure 0007663017000004
  • Figure 0007663017000001
    Figure 0007663017000001
  • Figure 0007663017000002
    Figure 0007663017000002
Patent Text Reader

Abstract

To provide a composition recovery method of a molten salt composition with improved efficiency.SOLUTION: A composition recovery method of a molten salt composition used for chemical strengthening treatment of chemically strengthened glass includes loading an alkali metal ion adsorbent filled in a vessel for addition into the molten salt composition and vibrating the vessel for addition after the loading. The alkali metal ion adsorbent has a filling rate of 80% or less to the volume of the vessel for addition. The amount of loading of the alkali metal ion adsorbent into the molten salt composition is 2 mass% to 10 mass% to the whole amount of the molten salt composition. An amplitude L2 of the vibration is 30 mm or more.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for restoring the composition of a molten salt composition for chemically strengthening glass, and a method for producing chemically strengthened glass. [Background technology]

[0002] In recent years, glass with sufficient strength to withstand drops is required for use as cover glass for displays on mobile devices such as smartphones. Chemical strengthening is known as one of the methods for increasing the strength of glass, and active development of chemically strengthened glass with high surface compressive stress (CS) and large depth of compressive stress layer (DOL) has been underway.

[0003] In a general chemical strengthening treatment, a glass for chemical strengthening is immersed in a molten salt composition, and an alkali metal ion having a small ionic radius in the glass for chemical strengthening is exchanged with an alkali metal ion having a large ionic radius in the molten salt composition, forming a compressive stress layer on the surface of the glass for chemical strengthening to obtain chemically strengthened glass. In this case, if the chemical strengthening treatment is repeatedly performed in a bath of the same molten salt composition (hereinafter also referred to as a "molten salt bath"). The concentration of small alkali metal ions released from the glass for chemical strengthening in the bath increases. If the concentration of small alkali metal ions in the molten salt composition increases, ion exchange in the chemical strengthening treatment is not performed sufficiently or the rate of exchange decreases. In other words, there is a limit to the number of times that the chemical strengthening treatment can be performed in a bath of the same molten salt composition, and a method for extending the life (bath life) of the molten salt bath is being considered.

[0004] As a method for extending bath life, a method has been considered in which the concentration of small alkali metal ions in the molten salt composition is reduced by using an adsorbent capable of adsorbing alkali metal ions, and various adsorbents have been developed.

[0005] For example, Patent Document 1 describes that when chemically strengthening glass is subjected to a chemical strengthening treatment, glass and an alkali metal ion adsorbent are added simultaneously to a molten salt composition. Moreover, Patent Document 2 describes a molecular sieve capable of adsorbing impurity metal ions in a molten salt composition. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] US Patent Application Publication No. 2018 / 0057402 [Patent Document 2] U.S. Pat. No. 1,042,7945 Summary of the Invention [Problem to be solved by the invention]

[0007] However, detailed consideration has not been given to the conditions for using the alkali metal ion adsorbent, and there has been a demand for a method for more efficiently recovering the composition of a molten salt composition. Therefore, an object of the present invention is to provide a more efficient method for recovering the composition of a molten salt composition and a method for producing chemically strengthened glass. [Means for solving the problem]

[0008] The composition recovery method of the molten salt composition of the present invention is a composition recovery method of a molten salt composition used in a chemical strengthening treatment of a chemically strengthened glass, Adding an alkali metal ion adsorbent filled in an addition container to the molten salt composition; vibrating the dosing vessel after the dosing; the filling rate of the alkali metal ion adsorbent relative to the volume of the addition container is 80% or less; The amount of the alkali metal ion adsorbent added to the molten salt composition is 2% by mass to 10% by mass with respect to the total amount of the molten salt composition, The vibration has a vibration width L2 of 30 mm or more. In one embodiment of the composition recovery method for a molten salt composition of the present invention, the vibration width L2 is preferably 100 mm or more. In one embodiment of the composition recovery method for a molten salt composition of the present invention, the alkali metal ions adsorbed by the alkali metal ion adsorbent are preferably Na ions. In one embodiment of the composition recovery method for a molten salt composition of the present invention, the ratio L2 / L1 of the width L2 of the vibration to the depth L1 of the molten salt bath containing the molten salt composition is preferably 0.1 to 1.0. In one embodiment of the composition recovery method for a molten salt composition of the present invention, the vibration speed is preferably 4 mm / s to 50 mm / s. In one embodiment of the composition recovery method for a molten salt composition of the present invention, the time for which the addition vessel is vibrated is preferably 2 hours or more. In one embodiment of the composition recovery method for a molten salt composition of the present invention, the alkali metal ion adsorbent preferably contains a glass auxiliary having any one of the following first to fourth glass compositions. First composition: In terms of mass % based on oxides, it contains 52 to 95% SiO2 and 5 to 25% Na2O. Second composition: In terms of mass % based on oxides, it contains 52 to 95% SiO2 and 5 to 28% K2O. Third composition: In terms of mass % based on oxides, it contains 55 to 75% SiO2 and 20 to 45% Na2O. Fourth composition: In terms of mass % based on oxides, it contains 55 to 75% SiO2 and 20 to 45% K2O.

[0009] The method for producing chemically strengthened glass of the present invention is a method for producing chemically strengthened glass, comprising immersing glass for chemical strengthening in a molten salt composition to perform a chemical strengthening treatment, recovering the composition of the molten salt composition; The recovery of the composition is Adding an alkali metal ion adsorbent filled in an addition container to the molten salt composition; vibrating the dosing vessel after the dosing; the filling rate of the alkali metal ion adsorbent relative to the volume of the addition container is 80% or less; The amount of the alkali metal ion adsorbent added to the molten salt composition is 2% by mass to 10% by mass with respect to the total amount of the molten salt composition, The vibration has a vibration width L2 of 30 mm or more. Effect of the Invention

[0010] According to the composition recovery method for a molten salt composition and the method for producing chemically strengthened glass of the present invention, the concentration of a specific alkali metal ion can be efficiently reduced by applying vibration to an adsorbent under specified conditions, thereby more efficiently recovering the composition of the molten salt composition. [Brief description of the drawings]

[0011] [Figure 1] FIG. 1 is a diagram illustrating a schematic diagram of an example of a composition recovery method for a molten salt composition according to the present embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] Hereinafter, an embodiment of the composition recovery method for a molten salt composition according to the present invention will be described. However, the present invention is not limited to the following embodiment, and can be modified as desired without departing from the gist of the present invention.

[0013] In this specification, the "%" in the content of a glass component means mass % on an oxide basis. In this specification, when a numerical range is indicated using "to", it means that the range includes the numerical values ​​before and after it as the lower and upper limits. In this specification, "chemically strengthened glass" refers to glass after chemical strengthening treatment, and "glass for chemical strengthening" refers to glass before chemical strengthening treatment.

[0014] In the chemical strengthening treatment of glass, as described above, alkali metal ions with a small ionic radius in the glass for chemical strengthening (hereinafter also referred to as "small alkali metal ions") are exchanged with alkali metal ions with a large ionic radius in the molten salt composition (hereinafter also referred to as "large alkali metal ions"), forming a compressive stress layer on the surface of the glass for chemical strengthening to obtain chemically strengthened glass. More specifically, the chemical strengthening treatment is carried out using one or more ion exchanges selected from Li-Na exchange, Li-K exchange, and Na-K exchange. That is, the small alkali metal ions refer to Li ions when the above ion exchange is at least one of Li-Na exchange and Li-K exchange, and refer to Na ions when the above ion exchange is Na-K exchange. Furthermore, the large alkali metal ion refers to a Na ion when the above ion exchange is Li-Na exchange, and refers to a K ion when the above ion exchange is at least one of Li-K exchange and Na-K exchange.

[0015] The composition recovery method of a molten salt composition according to the present embodiment is a composition recovery method of a molten salt composition used in a chemical strengthening treatment of glass for chemical strengthening, and includes the following steps A and B. (Step A) A step of adding an alkali metal ion adsorbent filled in an addition container to the molten salt composition. (Step B) vibrating the addition vessel after the charging.

[0016] In the composition recovery method for a molten salt composition according to this embodiment, the filling rate of the alkali metal ion adsorbent relative to the volume of the addition container is 80% or less, the amount of the alkali metal ion adsorbent added to the molten salt composition is 2 mass% to 10 mass% relative to the total amount of the molten salt composition, and the vibration width L2 in the vibration is 30 mm or more.

[0017] The molten salt composition is used for chemical strengthening of glass for chemical strengthening, and is used as a molten salt bath in a state where it is placed in a predetermined container such as a melting furnace. The glass for chemical strengthening is immersed in the molten salt composition in the molten salt bath, thereby carrying out the chemical strengthening treatment.

[0018] The molten salt composition contains at least large alkali metal ions before the chemical strengthening treatment, and when the chemical strengthening treatment is performed, the concentration of small alkali metal ions in the molten salt composition increases and the concentration of large alkali metal ions decreases due to the above-mentioned ion exchange.

[0019] In this embodiment, the recovery of the composition of the molten salt composition means that, by using an alkali metal ion adsorbent (hereinafter also simply referred to as "adsorbent"), the concentration of small alkali metal ions in the molten salt composition in the molten salt bath is made smaller than that before the adsorbent was added, and the concentration of large alkali metal ions is made larger than that before the adsorbent was added. By recovering the composition of the molten salt composition, the number of times that chemical strengthening treatment can be performed in the same molten salt bath, i.e., the life (bath life) of the molten salt bath, can be extended. In addition, when the composition is restored by ion exchange between the large alkali metal ions contained in the adsorbent and the small alkali metal ions in the molten salt composition, the concentration of the small alkali metal ions in the molten salt composition decreases and the concentration of the large alkali metal ions increases simultaneously. Therefore, when such an adsorbent is used, it can be determined that the composition has been restored by confirming either the decrease in the concentration of the small alkali metal ions or the increase in the concentration of the large alkali metal ions.

[0020] (Process A) The composition recovery method for a molten salt composition according to this embodiment includes a step of adding an alkali metal ion adsorbent filled in an addition container to the molten salt composition.

[0021] In this embodiment, the adsorbent is charged into the molten salt composition in a state where it is filled in an addition container. By using the addition container, the adsorbent can be easily vibrated in the molten salt composition. Furthermore, by using the addition container, the vibration method can be easily controlled to appropriate conditions. In addition, the adsorbent can be easily charged and recovered, and the adsorbent can be efficiently used in a shape with a relatively large surface area, such as a granular shape.

[0022] The container for addition is not particularly limited as long as it has a structure that allows the adsorbent in the container to come into contact with the molten salt composition, but for example, a container having a mesh structure is preferred, and specifically, a container whose entire surface to be immersed in the molten salt is surrounded by a mesh structure, a container whose only part of the surface is surrounded by a mesh structure and whose other surfaces are surrounded by plates, etc. are included. The container for addition is preferably a container having a mesh structure from the viewpoint of efficiently contacting the adsorbent with the molten salt composition and increasing the amount of adsorption of small alkali metal ions. Examples of the mesh structure include a metal mesh such as stainless steel, a punched metal, a wire mesh, etc., and a metal mesh is preferred from the viewpoint of preventing leakage of fine particles into the molten salt bath.

[0023] The opening size and opening ratio of the metal mesh can be appropriately adjusted according to the shape of the adsorbent to be filled. For example, the opening size is preferably 0.005 mm or more, more preferably 0.01 mm or more, and even more preferably 0.02 mm or more from the viewpoint of efficient contact between the adsorbent and the molten salt composition. On the other hand, from the viewpoint of suppressing the adsorbent from flowing out of the addition container and preventing problems from occurring in the chemical strengthening treatment or the composition recovery treatment of the molten salt composition, the opening size is preferably 0.50 mm or less, more preferably 0.10 mm or less, and even more preferably 0.04 mm or less.

[0024] The shape of the addition vessel is not particularly limited, and may be various shapes such as a rectangular parallelepiped, a cube, a cylinder, a sphere, a triangular pyramid, etc. From the viewpoint of efficiently contacting a larger volume of molten salt, the shape of the addition vessel is preferably a rectangular parallelepiped. The size of the addition vessel may be appropriately changed depending on the size of the molten salt bath, the amount of adsorbent added, the number of addition vessels to be put into the molten salt composition, etc.

[0025] Furthermore, the addition vessel may have a lid for filling the adsorbent, a member for fixing the addition vessel to the molten salt bath, a member for enabling vibration, and the like, as necessary.

[0026] The shape of the adsorbent filled in the addition container is not particularly limited, and various shapes such as plate-like, rod-like, block-like, granular, agglomerated, flake-like, powder-like, etc. can be used. Here, the term "agglomerated" refers to a state in which a plurality of adsorbent particles are combined to form secondary particles, the term "granular" refers to a state in which each of the adsorbent particles is present separately without forming secondary particles, and the term "flaky" refers to a state in which each of the adsorbent particles is in the form of a flat small piece. From the viewpoint of efficient contact between the adsorbent and the molten salt composition and from the viewpoint of handling, the shape of the adsorbent is preferably granular, flake-like, or powder-like.

[0027] For example, when the adsorbent is granular, the particle size is preferably 0.125 mm or more, more preferably 0.25 mm or more, and even more preferably 0.5 mm or more, from the viewpoint of preventing the adsorbent from flowing out of the addition container and from the viewpoint of ease of handling. The particle size of the adsorbent is preferably 5.0 mm or less, more preferably 2.0 mm or less, from the viewpoint of efficient contact between the adsorbent and the molten salt composition. Here, the particle size of the adsorbent refers to the average particle size in terms of the sieve opening, and specifically refers to the average particle size measured by the following method. (method) Sieve A n The sieve aperture is a n Then, sieves A1 to A5 are used, where a1 to a5 are as follows: a1=0.125mm, a2=0.25mm, a3=0.5mm, a4=1.0mm, a5=2.0mm The average particle size is calculated from the following formula: In the formula, "fall" means that the particles pass through the sieve openings and fall, and "remain" means that the particles do not pass through the sieve openings and remain on the sieve. (Formula) Average particle size (mm) = (mass fraction of particles that fell at A1) x a1 + (mass fraction of particles that remained at A1 and fell at A2) x {(a1 + a2) / 2} + (mass fraction of particles that remained at A2 and fell at A3) x {(a2 + a3) / 2} + (mass fraction of particles that remained at A3 and fell at A4) x {(a3 + a4) / 2} + (mass fraction of particles that remained at A4 and fell at A5) x {(a4 + a5) / 2} + (mass fraction of particles that remained at A5) x a5

[0028] The packing rate of the adsorbent relative to the volume of the addition container is 80% or less. With a packing rate of 80% or less, the adsorbent moves easily in the addition container during vibration, and the effect of vibration can be sufficient. The packing rate is preferably 75% or less, more preferably 70% or less, from the viewpoint of promoting alkali metal ion adsorption by vibration. Moreover, the packing rate is preferably 10% or more, more preferably 20% or more, and even more preferably 30% or more, from the viewpoint of increasing the amount of adsorbent added and promoting alkali metal ion adsorption. Here, the packing rate of the adsorbent relative to the volume of the addition container is a value (%) calculated as the ratio of the volume of the adsorbent to the volume of the addition container.

[0029] The amount of the adsorbent added to the molten salt composition is 2% by mass to 10% by mass with respect to the total amount of the molten salt composition. When the amount is 2% by mass or more, the amount of alkali metal ions adsorbed by the adsorbent can be sufficient. The amount is preferably 3% by mass or more, more preferably 4% by mass or more, and even more preferably 5% by mass or more. When the amount is 10% by mass or less, wear on the adsorbent-adding equipment can be reduced. The amount is preferably 9% by mass or less, more preferably 8% by mass or less, and even more preferably 7% by mass or less. Note that the amount of the adsorbent added can be appropriately increased or decreased depending on the type, shape, particle size, etc. of the adsorbent, the desired amount of small alkali metal ions to be adsorbed, the desired treatment time, etc., as long as it is within the above range.

[0030] The timing of adding the adsorbent to the molten salt composition is not particularly limited, and may be, for example, before the chemical strengthening treatment, during the chemical strengthening treatment, or after the chemical strengthening treatment. From the viewpoint of promoting alkali metal ion adsorption, the timing of adding the adsorbent to the molten salt composition is preferably after the chemical strengthening treatment. After the chemical strengthening treatment, the small alkali metal ion concentration in the molten salt composition becomes relatively large. By adding the adsorbent in such a state, it is preferable because the composition can be easily restored efficiently in a relatively short time. In addition, by adding the adsorbent after the chemical strengthening treatment, the addition container can be vibrated in a state where the glass for chemical strengthening (chemically strengthened glass) is not immersed in the molten salt bath, so that the risk of the glass for chemical strengthening (chemically strengthened glass) being damaged can be reduced.

[0031] The adsorbent may be divided and filled into a plurality of addition containers, or may be filled into one addition container. When divided and filled into a plurality of addition containers, the adsorbent filling rate in at least one addition container should be 80% or less. Preferably, the filling rate in all addition containers is 80% or less.

[0032] The position where the adsorbent is introduced into the molten salt bath is not particularly limited, and can be appropriately adjusted according to the structure of the molten salt bath and the method and direction of vibration. From the viewpoint of the diffusion distance of the alkali metal ions in the molten salt composition, the position where the adsorbent is introduced is preferably the center of the volume of the molten salt composition. As described later, the composition recovery method of the molten salt composition according to this embodiment includes a step of vibrating the addition vessel, and it is more preferable that the center between two points where the addition vessel reciprocates due to the vibration is located at the center of the volume of the molten salt composition.

[0033] (Process B) The composition recovery method for a molten salt composition according to this embodiment includes a step of vibrating the addition vessel after the above-mentioned step A.

[0034] The method of vibrating the addition vessel is not particularly limited, but may be, for example, a method of attaching a member to the addition vessel so that the addition vessel can be moved from the outside of the molten salt bath and vibrating the vessel. In this embodiment, an example of a method of vibrating the addition vessel is shown in FIG. 1. In FIG. 1, the molten salt bath 1 has a molten salt composition 3 in a vessel 30. The addition vessel 20 is filled with an adsorbent 2. In FIG. 1, the addition vessel 20 is placed in another vessel 40 that is larger than the addition vessel 20 and has an opening so that the molten salt composition 3 and the adsorbent 2 come into contact with each other. In this state, the addition vessel 20 can be vibrated by vibrating the part of the other vessel 40 that is not immersed in the molten salt composition 3 from the outside of the molten salt bath 1.

[0035] The width L2 of vibration when vibrating the addition vessel is 30 mm or more. Here, the width L2 of vibration refers to the length between two points where the addition vessel reciprocates due to vibration, in other words, the length of one way of reciprocation. The width L2 of vibration is parallel to the direction of vibration. For example, as shown in FIG. 1, when the direction of vibration of the addition vessel is parallel to the depth direction of the molten salt composition (molten salt bath), the width L2 of vibration is also parallel to this. And, even when the direction of vibration is inclined to the depth direction of the molten salt bath, that is, in a so-called oblique direction, the width L2 of vibration does not need to be the length of a component in a specific direction, such as a component parallel to the depth direction of the molten salt bath, but may be the actual length parallel to the direction of vibration. By making the width L2 of vibration 30 mm or more, the adsorbent in the addition vessel can be efficiently contacted with the molten salt composition, so that the amount of adsorption of small alkali metal ions can be sufficient. The width L2 of vibration is preferably 100 mm or more. The upper limit of the vibration amplitude L2 may be set according to the scale of the molten salt bath, and is not particularly limited, but is preferably 5 m or less. In FIG. 1, the addition vessel 20 moves in the same manner as the other vessels 40, so the vibration amplitude L2' of the other vessels 40 and the vibration amplitude L2 of the addition vessel 20 are the same, and the value of L2 can be adjusted by adjusting the value of L2'. The method of adjusting the vibration amplitude L2 can be appropriately changed according to the method of vibrating the addition vessel 20.

[0036] In addition, when a plurality of adding vessels are put into the molten salt bath, at least one adding vessel having a packing rate of the adsorbent of 80% or less is vibrated, and the vibration width L2 is set to 30 mm or more. Preferably, all of the adding vessels are vibrated, and the vibration width L2 is set to 30 mm or more.

[0037] The direction of vibration of the addition vessel is not particularly limited, and may be, for example, a direction parallel to the depth direction of the molten salt composition (molten salt bath) or a direction perpendicular to the depth direction. The direction of vibration can be appropriately set depending on the structure of the molten salt bath, etc. From the viewpoint of the feeding equipment, the direction of vibration is preferably a direction parallel to the depth direction of the molten salt composition.

[0038] The ratio L2 / L1 of the amplitude L2 of the vibration to the depth L1 of the molten salt bath containing the molten salt composition is preferably 0.1 to 1.0. The depth L1 of the molten salt bath refers to the depth L1 from the liquid surface to the bottom surface of the molten salt composition 3 in the molten salt bath 1, as exemplified in FIG. 1. The depth L1 of the molten salt bath generally changes with the scale of the molten salt bath, so L2 / L1 can be used as an index of the magnitude of vibration relative to the scale of the molten salt bath. That is, when L2 / L1 is 0.1 or more, the amplitude of vibration is likely to be sufficient relative to the scale of the molten salt bath, and the adsorbent and the molten salt composition can be more efficiently contacted, which is preferable. L2 / L1 is more preferably 0.15 or more, and even more preferably 0.25 or more. On the other hand, from the viewpoint of preventing problems such as the adsorbent being crushed and flowing out of the addition vessel or the molten salt composition leaking from the molten salt bath, L2 / L1 is preferably 1.0 or less, more preferably 0.8 or less, and even more preferably 0.6 or less.

[0039] The vibration speed is preferably 4 mm / s to 50 mm / s. A vibration speed of 4 mm / s or more is preferable because it provides the effect of stirring the molten salt composition. The vibration speed is more preferably 10 mm / s or more, and even more preferably 20 mm / s or more. In addition, from the viewpoint of preventing problems such as the adsorbent being crushed and flowing out of the addition vessel, or the molten salt composition leaking from the molten salt bath, the vibration speed is preferably 50 mm / s or less, more preferably 45 mm / s or less, and even more preferably 40 mm / s or less.

[0040] The time for vibrating the addition vessel is preferably 2 hours or more, more preferably 6 hours or more, and even more preferably 8 hours or more, from the viewpoint of sufficiently adsorbing the alkali metal ions, and is preferably 24 hours or less, more preferably 12 hours or less, and even more preferably 10 hours or less, from the viewpoint of reducing wear and tear on the equipment.

[0041] In addition, the amount of the adsorbent that can adsorb small alkali metal ions gradually decreases when the adsorbent is added to the molten salt composition, and the composition recovery effect of the molten salt composition may decrease. In this case, it is preferable to remove the adsorbent from the molten salt composition. That is, the composition recovery method of the molten salt composition according to this embodiment preferably includes a step of removing the adsorbent from the molten salt composition after the above-mentioned steps A and B.

[0042] The composition recovery method for a molten salt composition according to this embodiment includes a step of adjusting the filling rate of the adsorbent in the addition container and the amount of the adsorbent added relative to the amount of the molten salt composition within appropriate ranges, and includes a step of applying vibration to the addition container under predetermined conditions, thereby efficiently contacting the adsorbent with the molten salt composition. This improves the adsorption effect of small alkali metal ions by the adsorbent, and efficiently reduces the concentration of small alkali metal ions in the molten salt composition, thereby more efficiently recovering the composition of the molten salt composition than when, for example, the same type of adsorbent is used.

[0043] (Other embodiments) In addition to the composition recovery method for a molten salt composition according to the present embodiment described above, other embodiments in which the composition recovery method for a molten salt composition according to the present embodiment is modified as described below can be considered as methods capable of similarly efficiently recovering the composition of a molten salt composition.

[0044] Alternative embodiment 1: A method in which in the above step B, the molten salt composition is fluidized or vibrated instead of vibrating the addition vessel. In the above step B, the adsorbent and the molten salt composition are efficiently brought into contact with each other by vibrating the addition container, thereby efficiently recovering the composition of the molten salt composition. On the other hand, in another embodiment 1, it is considered that the adsorbent and the molten salt composition can be efficiently contacted with each other in the same manner as in the case of performing step B by flowing or vibrating the molten salt composition instead of vibrating the addition container, and the composition of the molten salt composition can be efficiently recovered. Examples of the method for flowing the molten salt composition include a method for flowing the molten salt composition by a screw or the like, and a method for moving the container of the molten salt bath to flow the molten salt composition in the bath. Examples of the method for vibrating the molten salt composition include a method using ultrasonic waves.

[0045] In addition, in Alternative Embodiment 1, a method may be used in which both the vibration of the addition vessel and the flow or vibration of the molten salt composition are performed, but it is preferable to adjust the conditions so as to avoid problems such as the adsorbent being crushed and flowing out of the addition vessel or the molten salt composition leaking from the molten salt bath.

[0046] In addition, in another embodiment 1, it is considered that the adsorbent and the molten salt composition can be efficiently contacted even when the adsorbent is added to the molten salt composition without using an addition container in the above step A. However, if an addition container is not used, fragments or fine powder derived from the adsorbent may flow in the molten salt composition when the adsorbent is crushed in the molten salt composition, and may come into contact with the glass for chemical strengthening, which may cause problems in the chemical strengthening process or defects in appearance. Therefore, it is preferable to adjust the shape of the adsorbent and the conditions of flow or vibration so as not to cause such problems. In addition, depending on the shape of the adsorbent, it may be inferior in terms of ease of introduction and removal of the adsorbent, so it is preferable to use an adsorbent in a shape that is easy to introduce and remove, such as a plate or block.

[0047] Alternative embodiment 2: A method in which in the above step A, a lump or other form of adsorbent is added to the molten salt composition without using an addition vessel, and in step B, the adsorbent is vibrated instead of using an addition vessel. In other embodiment 2, in order to vibrate the adsorbent itself added to the molten salt composition, it is preferable to use an adsorbent having a shape that can be vibrated (the amplitude of vibration can be controlled) after being added to the molten salt composition, such as a plate, rod, or block. In other embodiment 2, the surface area of ​​the adsorbent is likely to be smaller than when the same amount of granular adsorbent is used, and the adsorbent does not flow in the addition container, which is different from the case where an addition container is used. On the other hand, in other embodiment 2, by vibrating the adsorbent under predetermined conditions, the composition recovery effect of the adsorbent is larger than when such vibration is not performed, and its efficiency is thought to be improved. However, in other embodiment 2, when the adsorbent is crushed in the molten salt composition, fragments and fine powder derived from the adsorbent flow in the molten salt composition, which may cause problems in the chemical strengthening treatment, so it is preferable to adjust the shape of the adsorbent and the vibration conditions so as not to cause such problems.

[0048] (Alkaline metal ion adsorbent) As the alkali metal ion adsorbent used in this embodiment, various substances capable of physically or chemically adsorbing alkali metal ions can be used. As the alkali metal ion adsorbed by the alkali metal ion adsorbent, small alkali metal ions, that is, at least one of Li ions and Na ions, are preferred. When the small alkali metal ion is Li ion, the adsorbed alkali metal ion is preferably Li ion, and when the small alkali metal ion is Na ion, the adsorbed alkali metal ion is preferably Na ion.

[0049] Specific examples of the adsorbent include molecular sieves capable of adsorbing alkali metal ions, substances capable of adsorbing alkali metal ions by ion exchange reaction, etc. Examples of substances capable of adsorbing alkali metal ions by ion exchange reaction include inorganic compounds containing large alkali metal ions, and specific examples include glass auxiliary materials, crystalline materials, etc. From the viewpoint of ion exchangeability, the alkali metal ion adsorbent is preferably a glass auxiliary material.

[0050] As the glass auxiliary, for example, the above-mentioned glass containing large alkali metal ions can be used. When such a glass auxiliary is added to a molten salt composition containing small alkali metal ions, the large alkali metal ions in the glass auxiliary are exchanged with the small alkali metal ions in the molten salt composition. The glass auxiliary can adsorb the small alkali metal ions in the molten salt composition by such an ion exchange reaction. In addition, a glass auxiliary using such an ion exchange reaction is preferable in that it can greatly contribute to the extension of bath life because it can adsorb the small alkali metal ions in the glass auxiliary and simultaneously release the large alkali metal ions into the molten salt composition.

[0051] The glass composition of the glass auxiliary can be appropriately selected depending on the type of small alkali metal ion to be adsorbed. Specifically, the optimal composition of the glass auxiliary can be roughly classified into two types depending on the method of use. One type is a composition that prioritizes chemical durability over the amount of absorption of small alkali metal ions and the amount of release of large alkali metal ions, i.e., the amount of ion exchange. On the other hand, there is also a composition that prioritizes the amount of ion exchange over chemical durability. Also, intermediate compositions can be used. Furthermore, the optimal composition of the glass auxiliary differs depending on whether the small alkali metal ion to be ion exchanged is Li or Na. That is, the glass auxiliary preferably has any one of the following first to fourth glass compositions depending on the type of small alkali metal ions, etc. First composition: In terms of mass % based on oxides, it contains 52 to 95% SiO2 and 5 to 25% Na2O. Second composition: In terms of mass % based on oxides, it contains 52 to 95% SiO2 and 5 to 28% K2O. Third composition: In terms of mass % based on oxides, it contains 55 to 75% SiO2 and 20 to 45% Na2O. Fourth composition: In terms of mass % based on oxides, it contains 55 to 75% SiO2 and 20 to 45% K2O. These compositions will be specifically described below.

[0052] (First composition) First, a preferred range of the composition of the glass auxiliary giving priority to chemical durability (hereinafter also referred to as the "first composition") when the small alkali metal ion is Li will be described.

[0053] SiO2 is a component that constitutes the framework of the glass additive. In order to improve the stability of the glass auxiliary, the SiO2 content of the glass auxiliary of the first composition is preferably 52% or more, more preferably 54% or more, and further preferably 57% or more. On the other hand, in order to improve the meltability of the glass additive, the SiO2 content of the glass additive of the first composition is preferably 95% or less, more preferably 92% or less, and further preferably 90% or less.

[0054] Na2O is an essential component for Li-Na ion exchange. In order to increase the amount of ion exchange, the Na2O content of the glass auxiliary in the first composition is preferably 5% or more, more preferably 9% or more, and further preferably 11% or more. On the other hand, if the Na2O content is excessive, the chemical durability is likely to deteriorate. The Na2O content of the glass auxiliary of the first composition, which prioritizes chemical durability, is preferably 25% or less, more preferably 22% or less, and further preferably 20% or less.

[0055] Al2O3 is a component that inhibits ion exchange of alkali metal ions, but also improves chemical durability. The content of Al2O3 in the glass additive of the first composition may be 0%, but the glass additive of the first composition may contain Al2O3 as long as it is effective as a glass additive. When the glass auxiliary of the first composition contains Al2O3, the ratio of the content of Al2O3 to the content of Na2O (Al2O3 / Na2O) is preferably small, for example, preferably 2.0 or less, more preferably 1.5 or less, and even more preferably 1.1 or less. The content of Al2O3 is preferably 40% or less, more preferably 30% or less, and even more preferably 20% or less.

[0056] In order to obtain sufficient chemical durability, the total amount of SiO2 and Al2O3 is preferably 65% ​​or more, more preferably 70% or more, and even more preferably 75% or more. On the other hand, in order to increase the amount of ion exchange, the total amount of SiO2 and Al2O3 is preferably 95% or less, more preferably 92% or less, and even more preferably 90% or less.

[0057] The glass auxiliary having the first composition may contain, as required, in mass % on an oxide basis, 52 to 95% SiO2, 5 to 25% Na2O, 0 to 40% Al2O3, 0 to 15% MgO, 0 to 15% K2O, 0 to 10% P2O5, 0 to 10% B2O3, and 0 to 3% Li2O.

[0058] (Second Composition) Next, a preferred range of the composition of the glass auxiliary that prioritizes chemical durability when the small alkali metal ion is Na (hereinafter also referred to as the "second composition") will be described. Note that the glass auxiliary having the second composition can cause not only ion exchange with the small alkali metal ion being replaced with Na, but also ion exchange with the small alkali metal ion being replaced with Li. The SiO2 content is omitted since it is the same as the first composition.

[0059] KO is an essential component for Na-K ion exchange and is also known to contribute to K-Li ion exchange. In order to increase the amount of ion exchange, the K2O content in the glass auxiliary of the second composition is preferably 5% or more, more preferably 9% or more, and further preferably 11% or more. On the other hand, if the K2O content is excessive, the chemical durability is likely to deteriorate. The K2O content of the glass auxiliary of the second composition, which prioritizes chemical durability, is preferably 28% or less, more preferably 20% or less, and further preferably 16% or less.

[0060] Al2O3 is a component that inhibits ion exchange of alkali metal ions, but also improves chemical durability. The content of Al2O3 in the glass additive of the second composition may be 0%, but the glass additive of the second composition may contain Al2O3 as long as it is effective as a glass additive. When the glass auxiliary of the second composition contains Al2O3, the ratio of the content of Al2O3 to the content of K2O (Al2O3 / K2O) is preferably small, for example, preferably 2.0 or less, more preferably 1.5 or less, and even more preferably 1.1 or less. The content of Al2O3 is preferably 40% or less, more preferably 30% or less, and even more preferably 20% or less.

[0061] In order to obtain sufficient chemical durability, the total amount of SiO2 and Al2O3 is preferably 65% ​​or more, more preferably 70% or more, and even more preferably 75% or more. On the other hand, in order to increase the amount of ion exchange, the total amount of SiO2 and Al2O3 is preferably 95% or less, more preferably 92% or less, and even more preferably 90% or less.

[0062] The glass auxiliary having the second composition may contain, as required, in mass % on an oxide basis, 52 to 95% SiO2, 5 to 28% K2O, 0 to 40% Al2O3, 0 to 15% MgO, 0 to 10% P2O5, 0 to 10% B2O3, 0 to 3% Li2O, and 0 to 30% Na2O.

[0063] (Third composition) Next, a preferred range of the composition of the glass auxiliary agent giving priority to the ion exchange amount (hereinafter also referred to as the "third composition") when the small alkali metal ion is Li will be described.

[0064] SiO2 is a component that constitutes the framework of the glass additive. In order to improve the stability of the glass, the SiO2 content of the glass auxiliary in the third composition is preferably 55% or more, more preferably 60% or more, and further preferably 65% ​​or more. On the other hand, in order to improve the meltability of the glass, the SiO2 content of the glass auxiliary of the third composition is preferably 75% or less, more preferably 73% or less, and further preferably 69% or less.

[0065] Na2O is an essential component for Li-Na ion exchange. In order to increase the amount of ion exchange, the Na2O content of the glass auxiliary in the third composition is preferably 20% or more, more preferably 25% or more, and further preferably 30% or more. On the other hand, if the Na2O content is excessive, the chemical durability is likely to deteriorate. The Na2O content of the glass auxiliary in the third composition is preferably 45% or less, more preferably 40% or less, and further preferably 35% or less.

[0066] Al2O3 is a component that inhibits the ion exchange of alkali metal ions, but also improves chemical durability. The content of Al2O3 in the glass auxiliary of the third composition is preferably 0%, but the glass auxiliary of the third composition may contain Al2O3 as long as it is effective as a glass auxiliary. When the glass auxiliary of the third composition contains Al2O3, the ratio of the Al2O3 content to the Na2O content (Al2O3 / Na2O) is preferably small, for example, preferably 0.3 or less, more preferably 0.2, and further preferably 0.1 or less.

[0067] In order to obtain sufficient chemical durability, the total amount of SiO2 and Al2O3 is preferably 60% or more, more preferably 65% ​​or more. On the other hand, in order to increase the amount of ion exchange, the total amount of SiO2 and Al2O3 is preferably 80% or less, more preferably 75% or less, and even more preferably 70% or less.

[0068] The glass auxiliary having the third composition may contain, as required, in mass % on an oxide basis, 55 to 75% SiO2, 20 to 45% Na2O, 0 to 40% Al2O3, 0 to 10% MgO, 0 to 10% K2O, 0 to 10% P2O5, 0 to 10% B2O3, and 0 to 3% Li2O.

[0069] (Fourth composition) Next, a preferred range of the composition of the glass auxiliary agent prioritizing the amount of ion exchange when the small alkali metal ion is Na (hereinafter also referred to as the "fourth composition") will be described. Note that the glass auxiliary agent having the fourth composition can cause not only ion exchange with the small alkali metal ion being Na, but also ion exchange with the small alkali metal ion being Li. The SiO2 content is omitted since it is the same as the third composition.

[0070] KO is an essential component for Na-K ion exchange and is also known to contribute to K-Li ion exchange. In order to increase the amount of Na absorption, the content of K2O in the glass auxiliary of the fourth composition is preferably 20% or more, more preferably 25% or more, and further preferably 30% or more. On the other hand, if the K2O content is excessive, the chemical durability is likely to deteriorate. The K2O content of the glass auxiliary of the fourth composition is preferably 45% or less, more preferably 40% or less, and further preferably 35% or less.

[0071] Al2O3 is a component that inhibits ion exchange of alkali metal ions, but also improves chemical durability. The content of Al2O3 in the glass additive of the fourth composition may be 0%, but the glass additive of the fourth composition may contain Al2O3 as long as it is effective as a glass additive. When the glass auxiliary of the fourth composition contains Al2O3, the ratio of the Al2O3 content to the K2O content (Al2O3 / K2O) is preferably small, for example, preferably 0.3 or less, more preferably 0.2, and further preferably 0.1 or less.

[0072] In order to obtain sufficient chemical durability, the total amount of SiO2 and Al2O3 is preferably 60% or more, more preferably 65% ​​or more. On the other hand, in order to increase the amount of ion exchange, the total amount of SiO2 and Al2O3 is preferably 80% or less, more preferably 75% or less, and even more preferably 70% or less.

[0073] The glass auxiliary having the fourth composition may contain, as required, in mass % on an oxide basis, 55 to 75% SiO2, 20 to 45% K2O, 0 to 40% Al2O3, 0 to 10% MgO, 0 to 10% P2O5, 0 to 10% B2O3, 0 to 3% Li2O, and 0 to 30% Na2O.

[0074] More preferred embodiments of the glass auxiliary common to the first to fourth compositions are as follows.

[0075] The glass auxiliary may contain other components within the range in which the effects of the present invention are achieved. For example, the glass auxiliary may contain N, F, S, Cl, etc.

[0076] The glass auxiliary preferably has a total amount of SiO2 and Al2O3 of 60% or more. Since the glass auxiliary has a relatively large total amount of SiO2 and Al2O3 of 60% or more, the reaction with water in the molten salt composition is reduced. This makes it possible to suppress an increase in pH of the molten salt composition due to the addition of the glass auxiliary. If the pH of the molten salt composition increases, problems may occur in the appearance of the chemically strengthened glass obtained using such a molten salt composition. The total amount of SiO2 and Al2O3 of the glass auxiliary is preferably 65% ​​or more.

[0077] In addition, the glass auxiliary is preferably a glass mainly composed of an oxide of an element with an atomic number of less than 20, more specifically, a glass mainly composed of SiO2, Al2O3, Na2O, P2O5, B2O3, MgO and K2O. Specifically, the total content of SiO2, Al2O3, Na2O, P2O5, B2O3, MgO and K2O in the glass composition is preferably 95% or more. By having such a composition, as described below, the effect of recovering the composition of the molten salt composition is particularly high, which is preferable. In addition, the elution of ions that inhibit chemical strengthening is particularly reduced, which is preferable because it greatly contributes to extending the bath life.

[0078] First, trivalent or pentavalent ions function as network modifiers of the glass auxiliary, but large ions with atomic numbers exceeding 20 are difficult to move in the Si skeleton, and the presence of such elements inhibits the movement of alkali metal ions in the glass auxiliary. In other words, the inclusion of large ions with atomic numbers exceeding 20 reduces the ion exchange capacity of the glass auxiliary, and the effect of restoring the composition of the molten salt composition is reduced. In addition, divalent ions such as CaO and SrO do not significantly reduce the ion exchange amount of the glass auxiliary, but when they are dissolved in the molten salt composition, they remain on the surface of the glass to be chemically strengthened and inhibit the chemical strengthening treatment. In this case, even if the composition of the molten salt composition can be restored by ion exchange, the chemical strengthening treatment using the molten salt composition is affected, so the bath life extension effect is small.

[0079] Therefore, in order to ensure an excellent bath life extension effect in the glass auxiliary, it is preferable that the total content of SiO2, Al2O3, Na2O, P2O5, B2O3, MgO and K2O, which are components consisting of elements with an atomic weight of less than 20, is 95% or more. Moreover, the total content of SiO2, Al2O3, Na2O, P2O5, B2O3, MgO and K2O in the glass auxiliary is more preferably 96% or more, and further preferably 98% or more, with no particular upper limit and it may be 100%.

[0080] As described above, the total content of elements having an atomic weight of 20 or more in the glass auxiliary is preferably small, preferably 5% or less, more preferably 3% or less, and even more preferably 1% or less. Examples of elements having an atomic weight of 20 or more include Ti, Cr, Mn, Fe, Co, Ni, Cu, Zn, Y, La, Gd, Ca, Sr, Ba, Zr, Ta, W, etc.

[0081] More specific preferred compositions of the glass auxiliary include, for example, the following compositions (A) and (B).

[0082] Composition (A) In terms of mass% based on oxides, SiO2 52-90%, Al2O3 0-40%, MgO 15% or less, K2O 15% or less, Li2O 3% or less, Na2O 5-25%, B2O3 less than 10% Contains 10% or less P2O5, A glass auxiliary having a total content of the above oxides of 95% or more and a total content of SiO2 and Al2O3 of 65% to 95%.

[0083] Composition (B) In terms of mass% based on oxides, SiO2 55-75%, Na2O 20-45%, Al2O3 / Na2O is 0.3 or less, MgO 10% or less, K2O 10% or less, Li2O 3% or less, B2O3 less than 10% Contains 10% or less P2O5, A glass additive having a total SiO2 and Na2O content of 95% or more and a total SiO2 and Al2O3 content of 60-80%.

[0084] (Molten Salt Composition) The temperature of the molten salt composition in this embodiment is not particularly limited as long as it is within a temperature range in which the composition can be restored by the adsorbent. For example, when the adsorbent is the above-mentioned glass auxiliary, the temperature of the molten salt composition is preferably 350°C or higher, more preferably 400°C or higher, and even more preferably 420°C or higher, from the viewpoint of promoting ion exchange. In addition, in consideration of the decomposition of the molten salt, the temperature of the molten salt composition is preferably 500°C or lower, more preferably 475°C or lower, and even more preferably 460°C or lower.

[0085] As described above, the molten salt composition may contain at least a large alkali metal ion, i.e., at least one of Na ion and K ion, and the type of ion is not particularly limited. The molten salt composition generally contains at least one of a nitrate, for example, sodium nitrate and potassium nitrate.

[0086] (Chemically strengthened glass) The chemically strengthened glass that is chemically strengthened with a molten salt composition in this embodiment will be described. The glass for chemical strengthening may contain at least one of Li2O and Na2O, and various glasses may be used as long as the glass has a composition that allows strengthening by molding and chemical strengthening treatment. Examples of the glass for chemical strengthening include aluminosilicate glass, soda-lime glass, borosilicate glass, lead glass, alkali barium glass, and aluminoborosilicate glass. Specifically, for example, glass containing 50 to 80% SiO2, 2 to 25% Al2O3, 0 to 20% Li2O, 0.1 to 18% Na2O, 0 to 10% K2O, 0 to 15% MgO, 0 to 5% CaO, 0 to 5% P2O5, 0 to 5% B2O3, 0 to 5% Y2O3, and 0 to 5% ZrO2, expressed in mole percentage based on oxides, may be used as the glass for chemical strengthening.

[0087] In order to obtain chemically strengthened glass having a high CS and a large DOL and particularly high strength by chemical strengthening treatment, it is preferable to use a glass for chemical strengthening containing a large amount of small alkali metals to increase the amount of ion exchange during chemical strengthening. The content of the small alkali metals in the glass for chemical strengthening, i.e., at least one of Li2O and Na2O, may be, for example, 1% or more, 3% or more, or 5% or more.

[0088] The thickness and shape of the chemically strengthened glass are not particularly limited. The chemically strengthened glass may have various shapes, such as a flat plate shape having a uniform plate thickness, a shape having a curved surface on at least one of the front and back sides, and a three-dimensional shape having a bent portion, and may be subjected to mechanical processing such as cutting, edge processing, and drilling according to the application. The specific shape of the chemically strengthened glass is not particularly limited, but for example, the thickness is preferably 0.2 mm or more, and preferably 0.7 mm or more. The thickness of the chemically strengthened glass is preferably 5 mm or less, more preferably 3 mm or less, and even more preferably 2 mm or less.

[0089] (Method of manufacturing chemically strengthened glass) The present invention also relates to a method for producing chemically strengthened glass. The method for producing chemically strengthened glass according to the present embodiment is a method for producing chemically strengthened glass, which includes immersing glass for chemical strengthening in a molten salt composition to perform a chemical strengthening treatment (chemical strengthening treatment step), and includes recovering the composition of the molten salt composition (composition recovery step). In the method for producing chemically strengthened glass according to this embodiment, the recovery of the composition includes introducing an alkali metal ion adsorbent filled in an adding container into the molten salt composition and vibrating the adding container after the introducing, wherein the filling rate of the alkali metal ion adsorbent relative to the volume of the adding container is 80% or less, the amount of the alkali metal ion adsorbent introduced into the molten salt composition is 2 mass% to 10 mass% relative to the total amount of the molten salt composition, and the vibration width L2 in the vibration is 30 mm or more.

[0090] In the chemical strengthening process, the glass for chemical strengthening is immersed in a molten salt composition to perform the chemical strengthening process. The preferred embodiment of the glass for chemical strengthening is the same as described above. As described above, the molten salt composition may be a molten salt composition containing at least a large alkali metal ion, i.e., at least one of Na ion and K ion. The molten salt composition generally contains at least one of nitrates, such as sodium nitrate and potassium nitrate.

[0091] In the chemical strengthening treatment, the treatment time, the temperature of the molten salt composition, etc. can be appropriately adjusted according to the desired stress profile. For example, the treatment time is preferably 0.5 to 6 hours, and the temperature of the molten salt composition is preferably 400 to 500°C.

[0092] The method for producing chemically strengthened glass according to this embodiment includes a composition recovery step. In the composition recovery step, the composition of the molten salt composition used or used in the chemical strengthening treatment step is recovered. The method for recovering the composition in the composition recovery step is the same as the composition recovery method of the molten salt composition according to the embodiment described above, and the preferred aspects are also the same.

[0093] In the method for producing chemically strengthened glass according to this embodiment, the composition recovery step may be performed before the chemical strengthening treatment step, the composition recovery step may be performed simultaneously with the chemical strengthening treatment step, or the composition recovery step may be performed after the chemical strengthening treatment step. From the viewpoint of suppressing damage to the glass for chemical strengthening, etc., and from the viewpoint of efficiently performing the composition recovery step, it is preferable that the composition recovery step is performed after the chemical strengthening treatment step. From the same viewpoint, the chemical strengthening treatment step preferably includes a step of removing the glass for chemical strengthening (chemically strengthened glass), and the timing of removing the glass is more preferably before the composition recovery step. When a composition recovery step is performed before the chemical strengthening treatment step, or when a chemical strengthening treatment step is further performed after the chemical strengthening treatment step and the composition recovery step, the composition recovery step is preferably performed to remove the additive container from the viewpoint of suppressing damage to the chemically strengthened glass.

[0094] The method for producing chemically strengthened glass according to this embodiment includes at least one chemical strengthening treatment step and one composition recovery step, but each step may be included multiple times. In that case, each step may be included consecutively or alternately. In addition, the method may further include a known step generally performed in the production of chemically strengthened glass, as long as it does not impair the effects of the present invention.

[0095] According to the method for producing chemically strengthened glass according to the present embodiment, the life of the molten salt bath is extended by including the composition recovery step, so that the number of times chemical strengthening treatments can be performed using the same molten salt bath can be increased, and chemically strengthened glass can be produced efficiently.

[0096] The chemically strengthened glass produced by the method for producing chemically strengthened glass according to this embodiment is useful for the interior of automobiles, airplanes, etc., and liquid crystal display devices equipped with a touch panel function, such as mobile liquid crystal terminals represented by smartphones, liquid crystal display devices installed in vehicles, and liquid crystal display devices for personal computers. EXAMPLES

[0097] The following examples of the present invention will be described in detail, but the present invention is not limited thereto. In the examples, "ppm" means "ppm by mass." Examples 1 to 6 are examples, and Examples 7 to 10 are comparative examples.

[0098] (Preparation of Molten Salt Composition) Molten salt compositions (1) and (2) were prepared under the following conditions to simulate the state of the molten salt composition after chemical strengthening treatment, assuming a chemical strengthening treatment in which the small alkali metal ion is Na and the large alkali metal ion is K. Molten salt composition (1): KNO3 (Otsuka Chemical Co., Ltd.) 36.0 kg K2CO3 (Kanto Chemical Co., Ltd.) 3.2 kg NaNO3 (Kanto Chemical Co., Ltd.) 0.7 kg The above was placed in a cylindrical container (material: SUS304, dimensions: diameter 380 mm x height 360 mm) and made uniform at 435° C. The Na concentration was 5000 ppm. Molten salt composition (2): KNO3 (Otsuka Chemical Co., Ltd.) 268.0 kg K2CO3 (Kanto Chemical Co., Ltd.) 24.2 kg NaNO3 (Kanto Chemical Co., Ltd.) 7.8 kg The above was placed in a box-shaped container (material: SUS304, dimensions: length 500 mm x width 600 mm x height 760 mm) and kept in a uniform state at 435° C. The Na concentration was 7000 ppm.

[0099] [Measurement method] <Evaluation of ion concentration reduction rate> Approximately 5 g of each of the molten salt composition before and after the use of the adsorbent was taken out and diluted 10-fold with pure water, and the Na ion concentration was measured by atomic absorption spectrometry under the following conditions. From the measured values, the ratio of the Na ion concentration after use of the adsorbent to the Na ion concentration before use of the adsorbent was calculated as (Na ion concentration after use of the adsorbent / Na ion concentration before use of the adsorbent)×100 (%). Here, "before using the adsorbent" refers to the state before the adsorbent is added to the molten salt composition, and "after using the adsorbent" refers to the state after the adsorbent is added to the molten salt composition and the addition vessel is vibrated under the conditions described below. Equipment: Hitachi High-Technologies Corporation ZA3300 (Measurement conditions) Lamp current value: 10mA Wavelength: 589.0nm Slit: 0.4 nm Burner head: Standard burner Burner height: 7.5mm Frame: Air-acetylene Combustion support gas pressure: 160kPa Combustion gas flow rate: 2.0L / min Quantitative method: Calibration curve method

[0100] The molten salt composition (1) or (2) was used with an alkali metal ion adsorbent according to the methods of Examples 1 to 10 shown below, and the rate of decrease in ion concentration was evaluated by the above-mentioned method.

[0101] [Example 1] 40 kg of the molten salt composition (1) was placed in a melting furnace having a cylindrical container (material: SUS304, dimensions: diameter 380 mm x height 360 mm) and heated to a homogenous state at 435°C to prepare a molten salt bath. The height from the bottom surface of the molten salt composition in the molten salt bath to the liquid surface (depth L1 of the molten salt bath) was 210 mm. Next, a basket (length 25 cm, width 25 cm, height 25 cm) using a SUS316 mesh (stainless steel mesh manufactured by AS ONE Corporation, mesh 300) was used as an addition container, and 2 kg of Na ion adsorbent (concentration 5% by mass relative to the molten salt composition) was placed in the basket as an adsorbent. This was placed near the center of the molten salt volume in the melting furnace, and was then added to the molten salt composition. The Na ion adsorbents used were those shown in Table 1 below. The Na ion adsorbents shown in Table 1 correspond to the above-mentioned glass auxiliary.

[0102] [Table 1]

[0103] The above-mentioned Na ion adsorbent was crushed by a jaw crusher manufactured by Mayekawa Industries Co., Ltd., and then charged into the addition container. The particle size distribution and average particle size of the crushed Na ion adsorbent were measured by the following method. (method) Sieve A n The sieve aperture is a n The sieves A1 to A5, in which a1 to a5 are as follows, were used. a1=0.125mm, a2=0.25mm, a3=0.5mm, a4=1.0mm, a5=2.0mm The particle size distribution of the Na ion adsorbent obtained using sieves A1 to A5 is shown in Table 2. x ~a yThe values ​​(mass%) shown in the "A x So A remains y It represents the "mass percentage of particles that fell at the specified temperature." Based on the particle size distribution obtained, the average particle size was calculated using the following formula, and the average particle size of the Na ion adsorbent was found to be 1.5 mm. (Formula) Average particle size (mm) = (mass fraction of particles that fell at A1) x a1 + (mass fraction of particles that remained at A1 and fell at A2) x {(a1 + a2) / 2} + (mass fraction of particles that remained at A2 and fell at A3) x {(a2 + a3) / 2} + (mass fraction of particles that remained at A3 and fell at A4) x {(a3 + a4) / 2} + (mass fraction of particles that remained at A4 and fell at A5) x {(a4 + a5) / 2} + (mass fraction of particles that remained at A5) x a5

[0104] [Table 2]

[0105] As shown in Fig. 1, the addition container was placed in another container that was larger than the addition container and had an opening so that the molten salt composition and the adsorbent would come into contact with each other, and the other container was then placed in the molten salt bath so that the addition container was immersed in the molten salt composition. The addition container was vibrated under the following conditions by moving the part of the other container that was not immersed in the molten salt composition from outside the molten salt bath. Temperature of molten salt composition: 435°C Vibration method: (Vibration width L2: 100 mm (50 mm up and down), vibration speed: 20 mm / s, vibration direction: parallel to the depth direction of the molten salt bath) Vibration time: 8 hours

[0106] [Examples 2-10] In Examples 2 to 10, the conditions were changed to those shown in Table 3, and the same operations as in Example 1 were carried out except for the following changes. In Example 6, the size of the melting furnace was changed to a box-shaped vessel (material: SUS304, dimensions: length 500 mm × width 600 mm × height 760 mm), and molten salt composition (2) was used. In Example 7, the addition vessel was held in the charged state for 8 hours without being shaken. In Example 10, the addition vessel was changed to a basket of a size that provided a 100% adsorbent loading rate.

[0107] [Table 3]

[0108] In Examples 1 to 6, which are working examples, the alkali metal ion adsorbent was used under appropriate conditions, and the composition of the molten salt composition was efficiently restored. On the other hand, in Comparative Examples 7 to 10, although the same alkali metal ion adsorbent as in the working examples was used, the conditions of use were not appropriate, and as a result, the ratio of the Na ion concentration after use of the adsorbent to that before use of the adsorbent was larger than in the working examples, resulting in poor efficiency of composition restoration. [Explanation of symbols]

[0109] 1 Molten salt bath 2. Alkaline metal ion adsorbents (adsorbents) 20 Addition container 3 Molten salt composition 30 containers 40 Other containers L1 Depth of molten salt bath L2 Vibration width

Claims

1. A composition recovery method for a molten salt composition used in a chemical strengthening treatment of a chemically strengthened glass, comprising: Adding an alkali metal ion adsorbent filled in an addition container to the molten salt composition; vibrating the dosing vessel after the dosing; the filling rate of the alkali metal ion adsorbent relative to the volume of the addition container is 10% or more and 80% or less; The alkali metal ion adsorbed by the alkali metal ion adsorbent is a Na ion, The amount of the alkali metal ion adsorbent added to the molten salt composition is 2% by mass to 10% by mass based on the total amount of the molten salt composition, The composition recovery method for a molten salt composition, wherein the vibration has a vibration width L2 of 30 mm or more.

2. 2. The method for recovering a composition of a molten salt composition according to claim 1, wherein the vibration width L2 is 100 mm or more.

3. The direction of the vibration is parallel to the depth direction of the molten salt bath containing the molten salt composition, 3. The method for recovering a composition of a molten salt composition according to claim 1, wherein a ratio L2 / L1 of a width L2 of the vibration to a depth L1 of the molten salt bath is 0.1 to 1.

0.

4. The method for recovering a composition of a molten salt composition according to any one of claims 1 to 3, wherein the vibration speed is 4 mm / s to 50 mm / s.

5. The method for recovering a composition of a molten salt composition according to any one of claims 1 to 4, wherein the time for vibrating the addition vessel is 2 hours or more.

6. The composition recovery method for a molten salt composition according to any one of claims 1 to 5, wherein the alkali metal ion adsorbent contains a glass auxiliary having a glass composition of either the second composition or the fourth composition below. Second composition: In mass % based on oxide, SiO 2 52 to 95%, K 2 Contains 5-28% O. Fourth composition: In mass% based on oxide, SiO 2 55 to 75%, K 2 Contains 20-45% O.

7. A method for producing chemically strengthened glass, comprising immersing a glass for chemical strengthening in a molten salt composition to perform a chemical strengthening treatment, recovering the composition of the molten salt composition; The recovery of the composition is Adding an alkali metal ion adsorbent filled in an addition container to the molten salt composition; vibrating the dosing vessel after the dosing; the filling rate of the alkali metal ion adsorbent relative to the volume of the addition container is 10% or more and 80% or less; The alkali metal ion adsorbed by the alkali metal ion adsorbent is a Na ion, The amount of the alkali metal ion adsorbent added to the molten salt composition is 2% by mass to 10% by mass based on the total amount of the molten salt composition, The method for producing chemically strengthened glass, wherein the vibration width L2 in the vibration is 30 mm or more.

Citation Information

Patent Citations

  • Method for producing chemically strengthened glass

    JP2021059481A

  • Ion sieve material, and methods of preparing and using the same

    US10427945B2

  • On-line Method for Stabilizing Surface Compressive Stress of Chemically-tempered Glass

    US20180057402A1

  • Life extension method for molten salt composition, manufacturing method for chemically strengthened glass, glass auxiliary agent, and raw material for glass

    WO2020218253A1